Practical exploration of BOPPPS model combined with situational teaching method in clinical training of intensive medicine: novel pedagogy and perception - Liu, Yanquan; Lian, Xiaolan; Chen, Xiaojun; Zeng, Minjuan; Yin, Yue; Lin, Jie (Frontiers in Medicine, 2024)
Objective: To explore the application value of bridge-in, learning objective, pre-assessment, participatory learning, post-assessment, and summary (BOPPPS) model combined with situational teaching method in the clinical teaching of intensive care unit (ICU), and to provide experience for the reform of ICU clinical teaching and standardized training of intensive medicine.Methods: A randomized trial was conducted using a multi-center, prospective cohort study. A total of 293 residential physicians in